VO#51: Approval of unit rates of non-schedule item for supplying, fabrication & installation of study nook work - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the approval of unit rates of non-schedule item for supplying, fabrication & installation of study nook at BRACU new campus building.